2013
DOI: 10.1371/journal.pgen.1003677
|View full text |Cite
|
Sign up to set email alerts
|

Mediator Directs Co-transcriptional Heterochromatin Assembly by RNA Interference-Dependent and -Independent Pathways

Abstract: Heterochromatin at the pericentromeric repeats in fission yeast is assembled and spread by an RNAi-dependent mechanism, which is coupled with the transcription of non-coding RNA from the repeats by RNA polymerase II. In addition, Rrp6, a component of the nuclear exosome, also contributes to heterochromatin assembly and is coupled with non-coding RNA transcription. The multi-subunit complex Mediator, which directs initiation of RNA polymerase II-dependent transcription, has recently been suggested to function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 51 publications
2
26
0
Order By: Relevance
“…In budding yeast, Mediator head subunits are co-transcriptionally required for heterochromatin assembly at the pericentromere, in which both noncoding RNA processing and nuclear exosome Rrp6 are involved. 73 These new findings regarding the noncanonical roles of Mediator complex, as summarized in Figure 1, have broadened our understanding of the regulatory roles of the Mediator complex far beyond transcription initiation.…”
Section: Mediator Complex As a Novel Regulator Of Mrna Processingmentioning
confidence: 98%
See 1 more Smart Citation
“…In budding yeast, Mediator head subunits are co-transcriptionally required for heterochromatin assembly at the pericentromere, in which both noncoding RNA processing and nuclear exosome Rrp6 are involved. 73 These new findings regarding the noncanonical roles of Mediator complex, as summarized in Figure 1, have broadened our understanding of the regulatory roles of the Mediator complex far beyond transcription initiation.…”
Section: Mediator Complex As a Novel Regulator Of Mrna Processingmentioning
confidence: 98%
“…69 Similarly, the CDK8 subunit also activates hypoxia-inducible genes by recruiting SECs, which contain AFF4 and CDK9, and alleviating RNA Pol II pausing. 81 Recently, our group also found that CDK9, which is the enzymatic subunit of the P-TEFb complex, could directly interact with the Mediator subunit MED23 in vitro and in vivo; ChIP-seq data revealed that P-TEFb [70][71][72] Mediator head NA co-transcriptional heterochromatin assembly 73 Others H3K36me3/MRG15 PTB Transcription/splicing 40 Histone variants NA Transcription/3 ′ end formation 52,53 DNA methylation/CTCF NA Transcription/splicing 54,55 occupancy was decreased at a set of Med23-targeted gene promoters in Med23-depleted cells. 67 Recently, the Mediator complex was also found to overcome the repressive effects of Gdown1 in transcriptional elongation.…”
Section: Mediator Complex As a Novel Regulator Of Mrna Processingmentioning
confidence: 99%
“…In the yeast S. pombe , Mediator has been linked to pericentromeric heterochromatin formation 143 . These studies suggest that Mediator functions by coordinating pol II-dependent ncRNA transcription with the RNAi machinery to help form and maintain heterochromatin domains 143-145 . Similarly, Mediator has been implicated in telomeric heterochromatin maintenance in the budding yeast S. cerevisiae .…”
Section: Mediator and Chromatin Architecturementioning
confidence: 99%
“…We explored the possibility that elevated primary transcripts upon Exosc8 knockdown reflects increased transcription. The exosome complex can function via epigenetic regulation 39 and noncoding RNA surveillance, 40 which impact transcription. We tested whether Exosc8 regulates serine 5-phosphorylated RNA Polymerase II (pSer5-Pol II) occupancy at the affected promoters.…”
Section: Exosc8 Suppresses Primary Erythroblast Maturationmentioning
confidence: 99%